Adaptive active fault-tolerant MPPT control of variable-speed wind turbine considering generator actuator failure. (December 2022) - Chen, Jian; Yao, Wei; Lu, Qun; Ren, Yaxing; Duan, Wenyong; Kan, Jiarong; Jiang, Lin
Abstract: In order to ensure that the wind power system (WPS) can realize maximum power point tracking (MPPT) under generator side fault, an MPPT control system with adaptive active fault tolerance capability is proposed in this paper. The basic idea of the proposed control strategy is that a perturbation term containing model uncertainties, system nonlinearities and unknown disturbances (generator actuator failure and disturbance torque) is estimated in real-time by a designed observer. The estimated perturbation is used for the compensation of actual perturbation. Then, an adaptive feedback linearizing control of variable-speed wind turbine (VSWT) system can be realized. Therefore, the control strategy neither requires detailed system model and full state measurements, nor relies on fault detection, diagnosis and isolation techniques when the generator actuator fails. Simulation results show that the proposed control scheme has smaller tracking error and better dynamic performance than the traditional PI control and MPPT control, and higher robustness against system parameter uncertainties, disturbance torque and generator actuator failure than the nonlinear static state feedback based MPPT (NSSF-MPPT) control, traditional PI control and MPPT control. Highlights: An adaptive fault-tolerant MPPT control (AAFT-MPPTC) is proposed for wind turbine. The AAFT-MPPTC increases energy conversion efficiency of WT under time-varying wind. The AAFT-MPPTC enhances robustness against generator actuator failure. The AAFT-MPPTC does not require the detailed system model and full state measurements. Simulation results verify the effectiveness of the proposed AAFT-MPPTC scheme.